(untitled) (Revista de Ciências Agroveterinárias, 2025)
Triticale is a cereal increasingly used in human and animal nutrition. However, weeds, especially ryegrass (Lolium multiflorum) and turnip (Raphanus raphanistrum e R. sativus), can reduce both grain yield and quality. In this context, this study aimed to evaluate the competitive ability of triticale cultivars (BRS Ulisses, BRS Minotauro, Embrapa 53, and BRS Resoluto) in the presence of ryegrass and turnip using the replacement series method. Fourteen experiments were conducted in a randomized block design with four replicates. The treatments consisted of different proportions of crop and weed plants (100:0, 75:25, 50:50, 25:75, and 0:100%) arranged as 24:0, 18:6, 12:12, 6:18, and 0:24 plants per pot. Competitiveness was analyzed using replacement series diagrams and relative competitiveness indices. At 50 days after emergence, plant height, leaf area, gas exchange, and shoot dry matter of the crop and weeds were measured. Competition occurred between triticale cultivars and the weed species, resulting in mutual negative impacts on the growth of the species within the community. The crop and weeds exhibited similar competitive mechanisms and demands for environmental resources. Overall, physiological variables were negatively affected as weed density increased. Interspecific competition had a greater detrimental effect on the morphophysiological traits of the species than intraspecific competition.